TURISMO CINEGÉTICO: ¿UNA ALTERNATIVA DE DESARROLLO SUSTENTABLE? - Tello-Leyva, Yesenia Maraí; Vázquez-Herrera, Sofia Elba; Juárez-Reina, Alejandro; González-Pérez, Manuel (European Scientific Journal, ESJ, 2015)
Many people distort hunting tourism. This activity is taken as a murder at will and for no other reason. There is the general public about huge disinformation. In Mexico, there are no quantitative or qualitative data on the economic, social and environmental benefits generated by this type of tourism in the country. This activity can be done legally in the management of Units for the Conservation of Wildlife (UCW). Integrated management is essential to carry out successful hunting. The aim is to link economic, social and environmental benefits generated by hunting tourism, with a focus on sustainable development. This approach improves the quality of life of farmers and creates an alternative to long-term diversified production. As a result, sustainable development is evident in the dependent rural areas and lack of satisfaction of their needs.